Perspectives of clinical pharmacists on the provision of pharmaceutical care through telepharmacy services during COVID-19 pandemic in Qatar: A focus group. - Eman Alhmoud; Dania Al Khiyami; Raja Barazi; Mohammed Saad; Ali Al-Omari; Ahmed Awaisu; Rasha El Enany; Moza Al Hail (PLoS ONE, 2022)
Background Coronavirus disease 2019 (COVID-19) pandemic created unprecedented pressures on healthcare systems and led to the widespread adoption of telepharmacy services, a practice that was not previously established in the state of Qatar. Objective The -study aimed to explore clinical pharmacists' (CPs) perspectives and experiences in utilizing telepharmacy for the provision of pharmaceutical care during the COVID-19 pandemic. Methods A descriptive, qualitative approach using face-to-face focus group (FG) discussions was used. CPs across Hamad Medical Corporation (HMC) were purposively invited to participate in the study. FG discussions were audio-recorded, transcribed verbatim, and validated. Transcripts were analyzed using inductive thematic analysis. Recruitment continued until a saturation point was achieved. Results We conducted five focus groups that included 23 CPs and led to seven themes. Overall, CPs reported inadequate preparedness for the practice of telepharmacy, which they perceived as challenging. The primary perceived benefits of telepharmacy were decreased infection exposure risk, improved quality of care, improved patients' satisfaction, and enhanced workplace efficiency and productivity. The main highlighted risks of telepharmacy were related to threatened patient confidentiality, missed pharmaceutical care opportunities, and negatively impacted professional rapport with other healthcare providers; and the major perceived challenges were low digital health literacy, complex illnesses and medication regimens, lack of standardized protocols, and inadequacy of resources and cultural resistance for virtual care. Participants recommended standardization and training, resource allocation, and proper service promotion as potential facilitators of telepharmacy practice. Conclusion The current study revealed that despite perceived barriers, pharmacists identified several benefits of telepharmacy and recommended potential facilitators that should be used to integrate and sustain the practice of telepharmacy in the future. Future studies should investigate the impact of telepharmacy on clinical pharmacy interventions and patient outcomes.